PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN STUDI PADA JASA KAMAR ALPHA HOTEL PEKANBARU - Sihombing, Yan Firstdyanti; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The success of a company depends on several interrelated components and supporting each other. The components are service quality, corporate image and customer loyalty. This research was conducted at Alpha Hotel Pekanbaru, as for the purpose of this study was to determine the influence of service quality and company image on customer loyalty (Study at Alpha’s Hotel Pekanbaru Room Service). service quality and corporate image as the independent variable (X1X2) while the customer loyalty as the dependent variable (Y). The problem in this research is the sale of Alpha’s Hotel Pekanbaru room service was fluctuated and tenden to decline each year, and does not even reach the sales target. Seen from the presentation realization sale services of a hotel room in the last 4  years. The research sample was taken of 100 respondents of the population was calculated using the Slovin formula. The data was getting from the questionnaire and subsequently processed to then be tested with statistics through SPSS. From the results which shows that service quality and corporate image have a positive and significant impact on customer loyalty at room service Alpha Hotel Pekanbaru.                                     Key words: Service Quality, Corporate Image, Customer Loyalty